THE â€œTHIRD SPACEâ€ OF EDUCATION: HISTORY OF HIZBUL WATHAN MUHAMMADIYAH 1918-1949 - Mu?arif, Mu?arif (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2019)
As a product of social practice, the presence of Hizbul Wathan Muhammadiyah successfully fills the void between the dysfunction of formal education institutions and society. It is the contemplation of the input-output oriented paradigm of former colonial education. Some graduates suffer from reality faltering when they are directly involved in society. Hizbul Wathan Muhammadiyah exists as the antithesis of the contradictory structure between formal schools and society. It fills the ?third space? of education by serving as the intermediary to facilitate distinctive values, norms, and collective consciousness?which differ from the general Scout movement. The ideology of religious humanism, nationalism, and patriotism in Hizbul Wathan Muhammadiyah has moved beyond others